AN AYURVEDIC APPROACH IN THE MANAGEMENT OF HYPERTHYROIDISM (AYUSHDHARA, 2021)
AYUSH healthcare providers are contributing a good spectrum of health care system to India and rendering relief to the health seekers of the rural as well urban area. India has very long time tradition of the use of this system. Ayurvedic system of healthcare is a big fraction of AYUSH healthcare that originated as well as developed in India.Hyperthyroidism is a chronic, hormonal disorder that may affect almost all tissues and organs. Hyperthyroidism has been managed optimally with modern drugs since long but it may produce various untoward effects on long usage.The aim of this review is to study the literature regarding herbal drugs that have been commonly used in Hyperthyroidism or similar symptoms. The modern as well as Ayurvedic literature was reviewed to explore herbal drugs pertaining to pharmacological effects and therapeutic benefits for hyperthyroidism. The present article is an effort to highlight the role of a plants particularly used in hyperactive thyroid gland, which have multifaceted pharmacological actions and therapeutic potential. This review may also be used for designing various clinical studies to serve the usefulness of plants in similar hormonal disorders.